Considering difference: clinician insights into providing equal and equitable burns care for Aboriginal and Torres Strait Islander children. (24th May 2021) - Fraser, Sarah; Grant, Julian; Mackean, Tamara; Hunter, Kate; Keeler, Ngara; Clapham, Kathleen; Edgar, Dale W.; Towers, Kurt; Teague, Warwick J.; Ivers, Rebecca
Abstract: Objective : To better understand issues driving quality in burn care related to equity of outcomes and equality of provision for Aboriginal and Torres Strait Islander children. Methods : Seventy‐six interviews with team members who provide care for Aboriginal and Torres Strait Islander children in six paediatric burn units across five Australian jurisdictions were completed. Interface research methodology within a qualitative design guided data collection and analysis. Results : Three themes were identified: i) Burn team members who identify the requirement to meet the specific needs of Aboriginal and Torres Strait Islander children and deliver differential care; ii) Burn team members who believe in equal care, but deliver differential care based on the specific needs of Aboriginal and Torres Strait Islander children; and iii) Burn team members who see little need for provision of differential care for Aboriginal and Torres Strait Islander children and rather, value the provision of equal care for all. Conclusion : Burn team members conflate equitable and equal care, which has implications for the delivery of care for Aboriginal and Torres Strait Islander children. Equitable care is needed to address disparities in post‐burn outcomes, and this requires clinicians, healthcare services and relevant system structures to work coherently and intentionally to reflect these needs. Implications for public health : Changes in health policy, the embedding of Aboriginal and Torres Strait Islander liaison officers in burn care teams and systems that prioritise critical reflexive practice are fundamental to improving care.